2010
DOI: 10.1029/2010jd014284
|View full text |Cite
|
Sign up to set email alerts
|

Observational characteristics of the tropopause inversion layer derived from CHAMP/GRACE radio occultations and MOZAIC aircraft data

Abstract: [1] In this study we discuss characteristics of the Northern Hemisphere (NH) midlatitude (40°N-60°N) tropopause inversion layer (TIL) based on two data sets. First, temperature measurements from GPS radio occultation data (CHAMP and GRACE) for the time interval 2001-2009 are used to exhibit seasonal properties of the TIL bottom height defined here as the height of the squared buoyancy frequency minimum N 2 below the thermal tropopause, the TIL maximum height as the height of the N 2 maximum above the tropopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
26
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 45 publications
16
26
1
Order By: Relevance
“…The median ozone mixing ratio in the UT is 60 ppb, median CO mixing ratio is 90 ppb, and median PV is 0.5 PVU. Within the LMS, the median values for O 3 (310 ppb), for CO (40 ppb), and for PV (7 PVU) are consistent with previous studies (Pan et al, 2004;Kunz et al, 2008;Brioude et al, 2009;Schmidt et al, 2010). …”
Section: Spatial and Temporal Data Coveragesupporting
confidence: 78%
See 2 more Smart Citations
“…The median ozone mixing ratio in the UT is 60 ppb, median CO mixing ratio is 90 ppb, and median PV is 0.5 PVU. Within the LMS, the median values for O 3 (310 ppb), for CO (40 ppb), and for PV (7 PVU) are consistent with previous studies (Pan et al, 2004;Kunz et al, 2008;Brioude et al, 2009;Schmidt et al, 2010). …”
Section: Spatial and Temporal Data Coveragesupporting
confidence: 78%
“…Since 2001, GPSRO data have been assimilated in numerical weather prediction models and reanalysis products. Schmidt et al (2010) characterized the tropopause inversion layer in the Northern Hemisphere with temperature profiles from in situ measurements and from the model for the period from 2001 to 2009 and concluded that the cold point at the tropopause agreed well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Zhang et al (2015) supports this hypothesis by showing inhibited upward propagation of inertia-gravity waves (IGWs) due to the TIL, with data from a single US radiosonde station. Also, the TIL is likely to inhibit the cross-tropopause exchange of chemical compounds: high static stability suppresses vertical motion and is corre-lated with strong trace gas gradients (Hegglin et al, 2009;Kunz et al, 2009;Schmidt et al, 2010). In the next paragraphs we briefly review what is known so far about the observed variability in the extratropical TIL and the mechanisms proposed for its formation/enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Also, static stability suppresses vertical motion and correlates with sharper trace gas gradients, inhibiting the cross-tropopause exchange of chemical compounds (Hegglin et al, 2009;Kunz et al, 2009;Schmidt et al, 2010). For these reasons, the TIL attracts increasing interest from the scientific community.…”
Section: Introductionmentioning
confidence: 99%